A Nominal Theory of the Nominal Rate of Interest and the Price Level - Marco Antonio Campos Martins (Journal of Political Economy, 1980)
[This paper develops a simple theory of nominal income and interest determination under the assumption that the only relevant distinction between money and bonds lies in their holding periods. Individuals take full account of the government budget constraint and do not concern themselves with discounting future tax liabilities associated with the issue of government bonds. According to this theory, the price of bonds is analogous to the price level, and the nominal rate of interest is determined by the bond/money ratio and bears no close relationship to the rate of expansion of the price level.]